2022
DOI: 10.1177/00033197221113158
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Prognostic Nutritional Index and Contrast-Associated Acute Kidney Injury in Patients With Non-ST Segment Elevation Myocardial Infarction Undergoing Coronary Angiography

Abstract: Prognostic nutritional index (PNI), consisting of inflammatory-nutritional parameters, has been investigated in terms of outcomes and renal function in patients with coronary artery disease. The objective of this study is to assess the predictive power of the PNI in predicting the risk for developing contrast-associated acute kidney injury (CA-AKI), an important complication following coronary angiography in patients with non-ST-elevation myocardial infarction (NSTEMI). The study population (336 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Subgroup analysis showed that the OR of CIN in patients without ACS was 2.45 (95% CI: 1.729 to 3.471), while the OR was 5.103 (95% CI:1.553 to 16.771) in those with ACS ( Figure 4 ). To support this finding, our further analysis of the PNI in patients with or without CIN also demonstrated a lower PNI in patients with CIN compared to those without (MD = -5.1, 95% CI: −6.87 to −3.33, p < 0.00001, I 2 = 96%, eight studies, 15,516 patients, sensitivity analysis: consistent; certainty of evidence: very low) ( Figure 5 ) ( 7 , 9 , 11 , 16 , 17 , 19 21 ).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Subgroup analysis showed that the OR of CIN in patients without ACS was 2.45 (95% CI: 1.729 to 3.471), while the OR was 5.103 (95% CI:1.553 to 16.771) in those with ACS ( Figure 4 ). To support this finding, our further analysis of the PNI in patients with or without CIN also demonstrated a lower PNI in patients with CIN compared to those without (MD = -5.1, 95% CI: −6.87 to −3.33, p < 0.00001, I 2 = 96%, eight studies, 15,516 patients, sensitivity analysis: consistent; certainty of evidence: very low) ( Figure 5 ) ( 7 , 9 , 11 , 16 , 17 , 19 21 ).…”
Section: Resultsmentioning
confidence: 90%
“…The male proportion varied among the studies with a range of 54.4 to 84.1%. Six studies enrolled fewer than 1,000 patients (range: 251 to 925) ( 7 , 11 , 15 , 17 , 19 , 20 ), while four recruited more than 1,000 patients (range: 1,823 to 4,391) ( 9 , 16 , 18 , 21 ). All studies used circulating creatinine concentrations to determine the incidence of CIN in their participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations